The Effect of Strategic Information Systems on Competitive Advantage for Branches of Jordanian Banks Operating in the Irbid City - Jordan - Al-Awawdeh, Waleed (The Arab Journal of Administration, 2019)
The aim of this study was to identify the impact of strategic information systems on the competitive advantage for Branches of Jordanian Banks Operating in the Irbid City/Jordan. Three elements of the stra- tegic information systems were investigated; Human Resources, Data and Information, and Information Technology. Furthermore, two indicators of competitive advantage were examined; Cost, and Differentia- tion. A field study was conducted to cover the population of fifty-seven branches of Jordanian Banks Oper- ating in the Irbid City/Jordan. Questionnaires were conducted to obtain data. The researcher distributed the questionnaire to three managers in each branch. )171(questionnaires were distributed, )165(were received back and )163(were valid for statically analysis. Many statistical methods like Descriptive methods, Coefficients Regression were used in this study. The study showed that there is a strong positive relationship between strategic information systems and the twoindicators of competitive advantage at a significant level of )0.01(. the relation between ele- ments of the strategic information systems and cost was stronger than the relation between elements of the strategic information systems and differentiation )0.779(. The study showed that the information technology variable has the greatest impact on competitive advantage with a significant level of )0.514(followed by data and information with a significant level of )0.200(and human recourses with a significant level of )0.174(.